Opportunities and Obstacles of a Healthy Diet from an Economic and Psychological Aspect - Nikolett Mihály; Nándor Komáromi; József Lehota (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The issue of healthy consumption is an extremely timely topic in today's fast-paced world. One of today's ruling trends is health consciousness and the expansion of the health market. The role of health for consumers has been appreciated. People spend more and more to preserve their health. The consequence of conscious consumption is that individuals can keep their physical and mental health for a longer time and can remain active, and accordingly, they can be involved in economic growth. In our quantitative research we studied what the connection between financial status, identity, financial consciousness and health consciousness are among women. Our results confirms that the income status, degree of consciousness and "identity" mostly influence the existence of a healthy diet. Furthermore, a strong correlation is found between health consciousness, financial attitude and a sense of overall well-being.
Keywords: E21; H31; H51; 330; consumption; health; household; management